A systematic revision of the five-spotted Hemichromis complex (Cichliformes: Cichlidae) from West Africa and Lower Guinea, with the description of a new species from Cameroon - (:unkn) unknown (My University, 2021)
The group of large five-spotted Hemichromis species from West Africa and Lower Guinea was revised using an integrative approach combining morphometry (measurements, meristics and colour patterns) and genetics (cytochrome b gene). Specimens from 100 populations were sorted into three main groups on the basis of morphological criteria. Samples from Lake Bosumtwi clustered together with others from West Africa in a large well-supported clade (bootstrap values and posterior probabilities: 98/96/100), both in morphometric and genetic analyses, raising again the hypothesis of synonymy of H. frempongi with H. fasciatus. Samples from southern Lower Guinea, including the type locality (Gabon) of H. elongatus, constituted a second weakly resolved cluster (64/38/51), resulting from a potential admixture of populations of diverse origins which share common morphological traits. Populations from northern Lower Guinea (Atlantic coastal basins) and the upper Chad basin in Cameroon formed a third strongly supported clade (99/100/100), which corresponds to a new species, Hemichromis camerounensis sp. nov., herein described.
Keywords: African Research